Legal Reconstruction of Hoax Regulation Concerning Drugs, Supplements, and Herbal Claims for Influenza A (H3n2) on Social Media Platforms - Helma WIdya; Hemransyah Alam (Sean Institute, 2025)
The widespread circulation of false information concerning drugs, supplements, and herbal remedies claiming to cure or prevent Influenza A (H3N2) on social media has become a serious legal and public health concern in Indonesia. The uncontrolled dissemination of such hoaxes not only misleads the public but also potentially endangers human health and undermines the credibility of legitimate medical institutions. Despite existing legal frameworks under the Electronic Information and Transactions Law (ITE Law) and Health Law, the regulatory approach to health-related misinformation remains fragmented and reactive. This study aims to analysed and reconstruct the legal framework governing the dissemination of hoax information related to drugs, supplements, and herbal treatments for Influenza A (H3N2) through social media. Using a juridical-normative method combined with a conceptual and statutory approach, this research examines the intersection between criminal law, health law, and cyber law. Primary data sources include relevant legislation such as Law No. 19 of 2016 concerning Electronic Information and Transactions (ITE Law), Law No. 36 of 2009 concerning Health, and related criminal provisions in the Indonesian Penal Code (KUHP). The results indicate that current regulations are insufficient in addressing the complexity of digital misinformation in the health sector. The absence of specific provisions regarding health-related hoaxes causes interpretative ambiguity, weak enforcement, and limited deterrent effect. Therefore, a legal reconstruction is required—integrating clearer definitions, proportional sanctions, and preventive mechanisms under a unified legal framework. This reconstruction should emphasize three key aspects: (1) strengthening regulatory coordination between health and communication authorities, (2)establishing clear accountability for content creators and distributors, and (3) developing digital literacy and early detection systems for health misinformation. The study concludes that reconstructing hoax regulations within the context of health communication is crucial to achieving legal certainty, public protection, and national health security.